2011
DOI: 10.1172/jci41514
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X receptor activation induces FGF19-dependent tumor aggressiveness in humans and mice

Abstract: The nuclear receptor pregnane X receptor (PXR) is activated by a range of xenochemicals, including chemotherapeutic drugs, and has been suggested to play a role in the development of tumor cell resistance to anticancer drugs. PXR also has been implicated as a regulator of the growth and apoptosis of colon tumors. Here, we have used a xenograft model of colon cancer to define a molecular mechanism that might underlie PXR-driven colon tumor growth and malignancy. Activation of PXR was found to be sufficient to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 66 publications
8
117
1
2
Order By: Relevance
“…Activation of PXR upregulated the antiapoptotic signaling molecules BAG3, BIRC2, and MCL-1, and downregulated the proapoptotic factors BAK1 and p53 (Zhou et al, 2008;Habano et al, 2011). Others showed that activation of PXR induced tumor aggressiveness in mice and humans in a fibroblast growth factor 19-dependent manner (Wang et al, 2011). Based on these studies, the role of PXR in colon cancer remains unclear, thus the need for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PXR upregulated the antiapoptotic signaling molecules BAG3, BIRC2, and MCL-1, and downregulated the proapoptotic factors BAK1 and p53 (Zhou et al, 2008;Habano et al, 2011). Others showed that activation of PXR induced tumor aggressiveness in mice and humans in a fibroblast growth factor 19-dependent manner (Wang et al, 2011). Based on these studies, the role of PXR in colon cancer remains unclear, thus the need for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It also interacts with transcription factors such as the small heterodimer partner, pregnane X receptor (PXR), hepatocyte nuclear factor 4a, and peroxisome proliferatoractivated receptor, which disturb the expression of their target genes thereafter (Prieur et al, 2005;Kim et al, 2008;Krausova et al, 2011;Sozio et al, 2011). In particular, the antagonistic effects of metformin on PXR may partly contribute to its speculated anticancer activity (Krausova et al, 2011;Wang et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…PXR has been reported to specifically activate the fibroblast growth factor 19 signal only in colon tumor cells, but not in normal intestinal cells, thereby enhancing their neoplastic characteristics (Wang et al, 2011). Our recent study has demonstrated that PXR immediately elicits the p38 MAPK signaling pathways after ligand treatment to stimulate morphological changes and migration in well differentiated HepG2 cells.…”
Section: Discussionmentioning
confidence: 81%